2011
DOI: 10.1111/j.1442-9071.2011.02506.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in tarsal plate fibrillar collagens and elastic fibre phenotype in floppy eyelid syndrome

Abstract: The findings of altered elastic fibre phenotype and collagen accumulation are consistent with an adaptive response to cyclic mechanical loading of the tarsal plate, rather than an aetiological feature. These findings are important in understanding how the tarsal ECM responds to mechanical loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 36 publications
0
10
0
2
Order By: Relevance
“…As we have shown previously using a range of ocular cells, including fibroblasts isolated from scarred tissue, 20 , 21 our in vitro contraction assay using soft collagen gels is a good reflection of the potential of the cells for scarring in vivo. 20 , 28 , 30 This implies that, upon tissue injury and local release of cytokines, presternal cells may have an inherent ability to generate more contracture and scarring—an observation in accord with clinical experience. Interestingly, when the cells’ properties were analyzed within more physiological engineered tissues at tensional homeostasis, resting presternal fibroblasts were found to have a lower intrinsic cellular contractile force compared with eyelid cells, generating a tissue of overall slightly lower stiffness.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…As we have shown previously using a range of ocular cells, including fibroblasts isolated from scarred tissue, 20 , 21 our in vitro contraction assay using soft collagen gels is a good reflection of the potential of the cells for scarring in vivo. 20 , 28 , 30 This implies that, upon tissue injury and local release of cytokines, presternal cells may have an inherent ability to generate more contracture and scarring—an observation in accord with clinical experience. Interestingly, when the cells’ properties were analyzed within more physiological engineered tissues at tensional homeostasis, resting presternal fibroblasts were found to have a lower intrinsic cellular contractile force compared with eyelid cells, generating a tissue of overall slightly lower stiffness.…”
Section: Discussionmentioning
confidence: 71%
“…This behavior is reminiscent of that of fibrotic fibroblasts isolated from the conjunctiva of patients with Floppy Eyelid Syndrome, whereby the diseased fibroblasts displayed increased collagen matrix contraction abilities, 21 despite the affected tissues of origin displaying a disorganized, much less stiff, matrix. 30 This suggests that whilst fibroblasts’ behavior is adaptable and intimately linked to tissue biomechanics, their propensity to scar may eventually be down to how they respond to the local stimuli upon wounding.…”
Section: Discussionmentioning
confidence: 99%
“…4,[6][7][8] The aetiology of FES is unknown, but histopathological studies have demonstrated altered tarsal plate elastic fibre phenotype and collagen accumulation. 8,9 At least in part, elastic fibre degradation occurs due to up-regulation of elastolytic matrix metalloproteinases, possibly induced by chronic nocturnal cyclical mechanical loading and hypoxia. 4,7,8,10 FES may be identified clinically using the Lateralising Eyelid Sleep Compression Study (LESCs) technique.…”
Section: Introductionmentioning
confidence: 99%
“…ise tarsal dokudaelastik liflerdeki azalmaya kollajen 1 ve 3 yoğunluğundaki artışın eşlik ettiğini saptamışlardır. 24 Elastik lifte görülen bu değişimin uvulofaringoplasti uygulanan TUAS hastalarından elde edilen uvula dokusunda görülen değişimle benzerlik gös-termesi bu iki hastalık arasındaki ilişkiyi desteklemektedir. [23][24][25] Schlotzer-Schrehardt ve ark.…”
unclassified
“…24 Elastik lifte görülen bu değişimin uvulofaringoplasti uygulanan TUAS hastalarından elde edilen uvula dokusunda görülen değişimle benzerlik gös-termesi bu iki hastalık arasındaki ilişkiyi desteklemektedir. [23][24][25] Schlotzer-Schrehardt ve ark. ise yaptıkları çalışmada, tarsta ve göz kapağı derisinde elastin miktarında azalmayla birlikte elastolitik enzimlerden matriks metalloproteinaz (MMP)-7 ve 9'un aktivitesinin arttığını göstermişlerdir.…”
unclassified